FERMENTASI SUBSTRAT TERENDAM AMPAS KELAPA UNTUK PEMBUATAN MANNOSA - Suryana Purawisastra; Erwin Affandi; Luxi R. Pasaribu (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1999)
The Submerged Fermentation of Coconut Kernel Residue to Produce Mannose.The submerged fermentation of coconut kernel residue was carried out to produce the mannose, since the residue contains a lot of the natural mannose. Whereas the mannose is widely used in pharmaceutical and cosmetic manufactures as the filing substance, in addition to its ability to reduce the number of pathogenic bacteria such as Escherichia coli, Vibrio cholera and Salmonella adhering to the intestinal tissue. The coconut kernel residue used in this experiment was the fresh home-made residue, which was washed using hot water to eliminate the coconut milk, dried and grounded to become flour. The Bacillus subtilis was used in the form of cell suspension for the fermentation. The fermentation was carried out in two steps. The first step was to optimize the volume of suspension, and the second step was to optimize the coconuts residue flour used in the fermentation medium. The result of the experiment shown that the fermentation of the residue to produce the mannose was carried out by the submerged fermentation, since the residue of coconut kernel is insoluble in the liquid medium. The optimal suspension of inoculum was 2% (v/v) used in the submerged substrate medium for fermentation of 48 hours fermentation in 37o C incubator. The optimal percentage of the residue coconut flour was used 0.5% (v/v) resulting 3.18 g mannose in 100 g of the residue fermented in dried matter.Keywords: submerged fermentation, coconut kernel residue, mannose.